Grenvillian massif-type anorthosites in the Sierras Pampeanas - Casquet, César (2005)
We report the discovery of massif-type anorthosites in the Andean basement of the Western Sierras Pampeanas of Argentina. U–Pb zircon dating (by sensitive high-resolution ion microprobe) of a cogenetic gabbronorite dyke yields ages of 1070 ± 41 Ma for igneous emplacement and 431 ± 40 Ma for metamorphism. These anorthosites are petrologically and geochemically comparable with those of the Grenville province of Laurentia. Palaeogeographical reconstructions of Rodinia at 1.0–1.1 Ga suggest that the Sierras Pampeanas anorthosites were part of a large anorthosite province in the late Mesoproterozoic.